The KM3NeT neutrino telescopes in the Mediterranean Sea: Current status and prospects focusing on KM3NeT/ORCA - Tzamariudaki Ekaterini (EPJ Web of Conferences)
The KM3NeT research infrastructure is building second-generation neutrino telescopes in the depths of the Mediterranean Sea. The KM3NeT/ARCA detector at a depth of about 3500 m off the coast of Sicily, Italy, focuses on the detection of high energy (E > TeV) neutrinos from astrophysical sources. The KM3NeT/ORCA detector at a depth of about 2500 m off the coast of Toulon, France, is aimed at studying low energy (E > GeV) atmospheric neutrinos for measuring the neutrino mass hierarchy and for gaining insight on fundamental neutrino properties. In this contribution, results obtained during the early stages of the detector construction as well as the expected performance of the completed detectors are presented.